2021
DOI: 10.1302/2633-1462.210.bjo-2021-0090.r1
|View full text |Cite
|
Sign up to set email alerts
|

Modular component exchange and outcome of DAIR for hip and knee periprosthetic joint infection

Abstract: Aims The aim of this meta-analysis is to assess the association between exchange of modular parts in debridement, antibiotics, and implant retention (DAIR) procedure and outcomes for hip and knee periprosthetic joint infection (PJI). Methods We conducted a systematic search on PubMed, Embase, Web of Science, and Cochrane library from inception until May 2021. Random effects meta-analyses and meta-regression was used to estimate, on a study level, the success rate of DAIR related to component exchange. Risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…13,14 A recent systematic review, which included 6,630 patients, reported that the overall success rate of dAir after thA and tKA was 67%. 15 there was an improvement of outcome with the passage of time, without a significant difference between primary and revision arthroplasties. in a multicentre, retrospective study from new Zealand, Zhu et al 13 reported a success rate of dAir after primary tKA of 66% (71/107) after a mean of 6.9 years.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…13,14 A recent systematic review, which included 6,630 patients, reported that the overall success rate of dAir after thA and tKA was 67%. 15 there was an improvement of outcome with the passage of time, without a significant difference between primary and revision arthroplasties. in a multicentre, retrospective study from new Zealand, Zhu et al 13 reported a success rate of dAir after primary tKA of 66% (71/107) after a mean of 6.9 years.…”
Section: Discussionmentioning
confidence: 80%
“…As previously described, the success rate of dAir was slightly lower after tKA in our cohort than after thA, but this difference was not statistically significant. 13,[15][16][17] because of the low sample size, we could not perform a robust subgroup analysis in an attempt to identify separate factors associated with failure for patients with a thA or tKA. we noted a higher bmi in patients who underwent a revision tKA.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of exchanging all mobile components and liners is considered to theoretically improve infection eradication by two means; first, to improve the exposure of the joint to aid debridement of all areas where a potential infectious focus is present, especially posterior aspects of the knee; 19 and second, replacing mobile parts to remove a potential site of bacterial adherence that cannot always be achieved by debridement and irrigation, limiting the bacterial load present in the joint. 15 Despite some research showing that replacing mobile components does not relate to improved outcomes, 27,30 a notable amount of literature reports significant improvements in implant survivability 4,19,28 and infection eradication in both early and late PJI. 18,28 Exchange of mobile components is an independent factor related to DAIR success.…”
Section: Component Exchangementioning
confidence: 99%
“…4,6,7 Treatment of PJIs with DAIR is based on mechanical cleaning of the implant surface and subsequent antibiotic therapy. Presently, success rates vary from 60% to 80%, 6,8 which leaves room for improvement. It is therefore paramount that new treatments for PJI are being developed.…”
Section: Introductionmentioning
confidence: 99%